Reverse IgM enzyme-linked immunosorbent assay (Reverse IgM-ELISA) for toxoplasmosis serodiagnosis - Mineo, José Roberto; Camargo, Mário Endsfeldz; Ferreira, Antonio Walter; Almeida, Gastão (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
A Reverse IgM enzyme linked immunosorbent assay (Reverse-IgM ELISA) was described in which polyvinyl microplates were sensitized with anti-immunoglobulin M (IgM) antibodies and then sequentially allowed to react with patient's serum, Toxoplasma gondii soluble antigen, peroxidase labeled specific F(ab')2 fragment and substrat. Measurement of activity of the solid phase bound enzyme conjugate was done by spectrofotometric reading of the final developed color. In a group of 69 sera samples from individuals with recently acquired toxoplasmosis, Reverse-IgM ELISA was positive in every case, showing higher geometric mean titer than others conventional serological tests. Furthermore false-negative IgM samples presented positive Reverse-IgM ELISA results even without adsorption with Staphylococcus aureus protein A . In a group of 104 sera samples from individuals with others pathologies, no interference was observed, even in the false-positive IgM samples due to the presence of IgM rheumatoid factor.